Novel Use of Optokinetic Chart Stimulation to Restore Muscle Strength and Function in a Bed Bound Traumatic Brain Injury Patient that was in a Vegetative State of Unconsciousness: A Case Study - Ciara R McConaghy; Benjamin Chitambira (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2015)
Introduction: Patients with severe traumatic brain injury are known to have poor outcomes. The prognosis is even worse if they remain vegetative or minimally conscious for months. The objective of this case report is to highlight the novel use of optokinetic chart stimulation to improve muscle strength and functional mobility in a patient who was in a vegetative state of unconsciousness for months after sustaining a severe traumatic brain injury and C7 spinal fracture. The patient could not open their eyes and breathed through a tracheostomy tube. Methodology: An optokinetic chart was moved in front of the patient: from side to side, up and down and finally forwards and backwards. This was supplemented with sensory interaction for balance once the patient could stand with assistance. Results: Oxford score improved from absent voluntary movements to 410/410 within one month after treatment had begun. GCS improved from 3/15 to 15/15 after treatment. Barthel index improved from 0/100 to 30/100 within 6 weeks and was 50/100 3 months post commencement of intervention. Conclusion: From having conventional therapy that centred on chest physiotherapy and suctioning of secretions in bed, the patient remarkably improved to mobilising with a wheeled zimmer walking aid and the assistance of one person. This is the first reported use of optokinetic stimulation in vegetative unconscious traumatic brain injury patients. Further research is required on the use of optokinetic chart stimulation in patients who are minimally conscious or vegetative after severe traumatic brain injuries.